Towards Interactive Debugging of Rule-based Entity Matching - Panahi, Fatemah; Wu, Wentao; Doan, AnHai; Naughton, Jeffrey F. (Proceedings of the 20th International Conference on Extending Database Technology (EDBT 2017), 2017)
Entity Matching (EM) identifies pairs of records referring to the same real-world entity. In practice, this is often accomplished by employing analysts to iteratively design and maintain sets of matching rules. An important task for such analysts is a “debugging” cycle in which they make a modification to the matching rules, apply the modified rules to a labeled subset of the data, inspect the result, and then perhaps make another change. Our goal is to make this process interactive by minimizing the time required to apply the modified rules. We focus on a common setting in which the matching function is a set of rules where each rule is in conjunctive normal form (CNF). We propose the use of “early exit” and “dynamic memoing” to avoid unnecessary and redundant computations. These techniques create a new optimization problem, and accordingly we develop a cost model and study the optimal ordering of rules and predicates in this context. We also provide techniques to reuse previous results and limit the computation required to apply incremental changes. Through experiments on six real-world data sets we demonstrate that our approach can yield a significant reduction in matching time and provide interactive response times.